The Influence of Parental Care Through The Application of Biblical Stories on The Social Abilities of Children Aged 4 - 6 Years at Kalam Kudus I Kindergarten, Jakarta - Yunita Damayanti; Brigita Puridawaty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to analyze how big is the influence of parental care through the application of Bible stories on the social abilities of children aged 4-6 years at Kalam Kudus I Kindergarten, Jakarta. Social abilities are an important aspect of children's development, because they influence the way they behaveinteracting with peers, sharing and collaborating, empathizing, speaking and listening, expressing emotions, and adapting. Seeing this,Parents play an important role in improving these social abilities. By using a Bible story approach in parenting, parents can help children develop their social skills. Researchers used quantitative research methods with a quasi-experimental non-equivalent control group design, which divided research subjects into two groups, namely the experimental group and the control group. The results of the research show that the application of Bible stories in parenting has a significant influence on the social abilities of children aged 4-6 years at Kalam Kudus I Kindergarten, Jakarta.